Effects of Land Ownership Disputes on Social Structure in Tehsil Dargai District Malakand - Nisar , Muhammad (Global Disclosure of Economics and Business, 2018)
The main objective of this research study was to ascertain the effect of land ownership disputes due to land commercialization and its effects on social structure in Tehsil Dargai, Khyber Pakhtunkhwa, Pakistan. Out of 291 respondents from civil suit/1 register of Tehsil Dargai, a sample size of 128 respondents was selected randomly through using the Mwakaje (2013) formula. Convenience sampling was used as a tool for data collection. The dependent variable (social structure) was cross tabulated with independent variable (land commercialization related disputes). Association of variables was ascertained by using Chi-square test. The study found a significant association between social structure and land ownership disputes due to urbanization (P= .045), population pressure (P=014), land considered a key asset of livelihood (P=0.000), agricultural commercialization (P=0.000) and increase in land prices (P=0.000). However, there was a non-significant relationship between social structure and migration into an area (P=0.200). The study concluded that the social structure is becoming weakening due to land disputes because of commercialization. People are becoming materialistic in their outlook and feel no hesitation in adopting unfair means to sell or force encroachment on other’s land which leads to the weakening of social bonds and hence social structure.